Characterization of thermo-responsive shape memory bio-based thermoplastic polyurethane (SMTPU) for 3D/4D printing applications - Yang Sook Jung; Jaehyeung Park; Sunhee Lee; Eun Joo Shin (Fashion and Textiles)
Abstract In recent years, significant advancements have been made in smart and multifunctional materials through the integration of 4D printing and shape memory polymers (SMPs). This article highlights key SMP fabrication technologies for 4D printing, focusing on the functionality of stimuli-responsive polymers. Bio-based thermoplastic polyurethanes are produced through the prepolymer polymerization method, with 100% bio-based polyester polyols, polypropylene succinate, and 1,3-propanediol by corn sugar. The resulting SMTPU, which contains bio-polyol in the soft segment, along with a chain extender and isocyanate (4,4-methylene diphenyl diisocyanate, MDI), demonstrates excellent shape recoverability even after significant deformation. Atomic force microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction were employed to analyze hydrogen bonding, microphase separation, and crystallinity, providing insights into the interactions between hard segments (HSs) and soft segments (SSs), an extent of phase separation, and a proportion of hydrogen-bonded urethane groups. The tensile strength of 15–21 MPa, elongation between 534 and 585%, and a hardness of 82–85 Shore A were shown. This study further explores the sustainability and unique properties of SMTPU, making it well-suited for shape memory applications at different temperatures with varying hard segment content. The findings are expected to contribute to future innovations and advancements in the field of 4D printing. Graphical Abstract